Green microfinance promoting sustainable development goals (SDGS) in Bangladesh - Uddin, Md Nazim; Hamdan, Hamdino; Kassim, Salina; Md Saad, Norma; Che Embi, Nor Azizan (2020)
This paper aims to examine microfinance and Sustainable Development Goals (SDGs) renewable for green microfinance development. Green microfinance Policy and encourages Microfinance Institutions (MFIs) to participate in providing green microfinance to promote environmental-friendly for substantial financial development in SDGs. Research objectives of this paper examine the relation of profitability with green microfinancing on MFIs in Bangladesh. The finding suggests that the significant aspects of green microfinancing are very much consistent with SDGs. Finally, the paper examines how far the MFIs in Bangladesh have been adopting the green microfinancing to measure the future of green microfinancing and SDGs for Bangladesh. First few to critically examine green microfinance from the perspectives of MFIs, this study is thought to be beneficial for the organizations and policymakers in the effort to evaluate the function and contribution of MFIs in addressing the primary environmental issues in Bangladesh. Moreover, through meticulous evaluation on the adherence of the existing green microfinance policy, this research can be expected to become the main one of the blueprints to encourage green MFIs in Bangladesh to become more included green microfinancing, to be able to attain both prosperity in this world.